The globalization of the cruise industry: a tale of ships. (2014) - ,
Abstract : Purpose – The paper aimed to explore the development of the North American and the European cruise industry. The paper is discursive and it covers philosophical discussions and comparative studies of others' work and thinking. The paper attempts to provide answers to the following questions. Is it a zero‐sum game? And does the rise of new tourism destinations imply the decline of some of the existing destinations?Design/methodology/approach – This paper employs literature and archival documents utilizing data from Berlitz Guides to Cruising 1992‐2013, Cruise Industry News Annuals 1995‐2013, and other sources were evaluated to draw conclusions.Findings – Cruising has evolved from a source of supplemental income into the fastest growing segment of the hospitality and tourism industry. The confluence of innovative ships, improved distribution channels, market awareness, and harbor facilities, has often resulted in rapid sustained expansion. Looking at the quantity and quality of major ships, their impact on the growth and globalization of the industry is illustrated.Practical implications – Ship numbers and deployment patterns can serve as precursors of growth. Analysis shows that quantitative and qualitative changes in permanently assigned ships signal transformative growth in a region's cruise market.Originality/value – The paper serves to identify regions and times for further investigation of impact. The paper is a concise chronicle of the development of the cruise industry and it serves as a basis for further in‐depth research.